The role of myeloid cell-derived PDGF-B in neotissue formation in a tissue-engineered vascular graft. (April 2017) - Onwuka, Ekene; Best, Cameron; Sawyer, Andrew; Yi, Tai; Heuer, Eric; Sams, Malik; Wiet, Matthew; Zheng, Hong; Kyriakides, Themis; Breuer, Christopher
Aim: Inflammatory myeloid lineage cells mediate neotissue formation in tissue-engineered vascular grafts, but the molecular mechanism is not completely understood. We examined the role of vasculogenic PDGF-B in tissue-engineered vascular graft neotissue development.Materials & methods: Myeloid cell-specific PDGF-B knockout mice (PDGF-KO) were generated using bone marrow transplantation, and scaffolds were implanted as inferior vena cava interposition grafts in either PDGF-KO or wild-type mice.Results: After 2 weeks, grafts from PDGF-KO mice had more remaining scaffold polymer and less intimal neotissue development. Increased macrophage apoptosis, decreased smooth muscle cell proliferation and decreased collagen content was also observed.Conclusion: Myeloid cell-derived PDGF contributes to vascular neotissue formation by regulating macrophage apoptosis, smooth muscle cell proliferation and extracellular matrix deposition.